‘To refer, not to characterise’: A synchronic look at the Son-of-Man logia in the Sayings Gospel Q - Llewellyn Howes (HTS Teologiese Studies/Theological Studies, 2013)
The article intends to address the Son-of-Man problem by applying Delbert Burkett’s ‘question of reference’ to those Son-of-Man logia that appear in the Sayings Gospel Q. A position is taken that recent philological approaches to the Son-of-Man problem have not been overly convincing, successful or helpful. Similarly, attempting to determine the authenticity of individual Son-of-Man sayings has not led to any form of scholarly consensus. In place of these approaches, a synchronic approach is defended and applied to the Son-of-Man sayings in Q, with interesting results.